The Power of Clickbait: Questioning Indonesian Online News Media’s Stand Point in the Digital Era - Rasta Bilqiis, Ritya; Thohiriyah, Thohiriyah (Universitas Negeri Semarang, 2020)
The digital era nowadays allows users to gain information easily and quickly. Many various kinds of search engines allow readers to find news in accordance with the information they need. However, in search engine usage, not all of the readers will look for the less popular news. According to Fintham, et al (2018) the readers only access the mainstream media sites with the reliability of a source of Uniform Resource Locator (URL). This has happened because those media has built a reputable image for the readers. However, the less popular media has limited entry-level in their search engines which results in their ways to change into clickbait strategy. Eye-catching headlines become the primary target in order to bring out the curiosity for the readers. This leads to change media’s position to be partisan where they make headlines that tend to focus on clicks only. The relevance of the news has not become a major priority. According to Muttaqin (2008) in writing news journalists are not allowed to enter personal opinions in written news. It clearly shows that the media’s position should be neutral. The news sites which only emphasize clicking need to be questioned. Therefore, this research is necessary to be conducted in order to analyze the standpoint of Indonesia’s online media through a post-truth perspective. Library research and close-reading methods are employed in this analysis. The result of the analysis shows that the position of the media in the digital age is increasingly unclear because most media no longer uphold the principles of journalism that Indonesian journalists present the news equally and fairly, including prioritizing accuracy, and not giving confusing facts and opinions.